2015
DOI: 10.1007/s12306-015-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

AIIMS test: a simple test to look for presence of palmaris longus

Abstract: Our proposed test to evaluate the presence of palmaris longus tendon is very simple and easy-to-understand manoeuvre with good sensitivity. It would be extremely useful in the preoperative planning in most of the reconstructive surgeries, should the palmaris longus tendon be harvested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…2 In this study, the AIIMS test showed the maximum number of 113 (82.4%) tendons in the right hand and 108 (78.8%) tendons in the left hand. Likewise, the prevalence of the agenesis of the PL tendon using the AIIMS test was found to be 24 (17.6%) in the right hand and 29 (21.2%) in the left hand and is comparable with the study conducted by Machhindra et al 7 where the overall prevalence of agenesis of the tendon was 20%. In this study, Thompson's test showed the presence of 109 (79.6%) tendons in the right hand and 106 (77.4%) tendons in the left hand.…”
Section: Discussionsupporting
confidence: 87%
“…2 In this study, the AIIMS test showed the maximum number of 113 (82.4%) tendons in the right hand and 108 (78.8%) tendons in the left hand. Likewise, the prevalence of the agenesis of the PL tendon using the AIIMS test was found to be 24 (17.6%) in the right hand and 29 (21.2%) in the left hand and is comparable with the study conducted by Machhindra et al 7 where the overall prevalence of agenesis of the tendon was 20%. In this study, Thompson's test showed the presence of 109 (79.6%) tendons in the right hand and 106 (77.4%) tendons in the left hand.…”
Section: Discussionsupporting
confidence: 87%
“…Palmaris longus and little finger superficial flexor varies anatomically in human body, as one may be present or both are absent in the hand and wrist [ 1 ]. These variations may be assessed by several clinical tests and these tests are more superior to the other according to some studies [ 2 3 4 5 6 7 8 ]. A recent study showed that different tests may suggest different results when the presence of Palmaris Longus is assessed by them [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared various clinical tests to detect the PL tendon (Kigera and Mukwaya, 2012; Kyung et al., 2012; Machhindra et al., 2015; Ndou et al., 2010; Sadeghifar et al., 2018), and three of these five also found Schaeffer’s standard test to be the most ‘accurate’ in detecting the PL tendon (Kigera and Mukwaya, 2012; Kyung et al., 2012; Sadeghifar et al., 2018). However, none of these studies verified the accuracy of the examination manoeuvres against surgical dissection or advanced imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examination accuracy may also be influenced by the examiner’s level of expertise. While the examiners in the present study are attending orthopaedic surgeons with over 60 years of combined experience, examiners in previous studies included medical school or physician assistant students (Kigera and Mukwaya, 2012; Sadeghifar et al., 2018) and first year orthopaedic residents (Machhindra et al., 2015). The most common difficulty reported in the examination for the presence of the PL is the misinterpretation of the flexor carpi radialis as the PL, and novice examiners are more susceptible to this mistake than experienced examiners (Sadeghifar et al., 2018; Sebastin and Lim, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation